compas-dev/compas_eve: v0.3.0 ... - Gonzalo Casas (Zenodo, 2023)
Added Added examples and more detailed documentation for installation and usage. Added BackgroundWorker class and BackgroundTask Grasshopper component to execute long-running tasks without blocking GH. Changed Fixed bug failing to get a str representation of Message on ipy Pinned Sphinx version for docs generation Removed ...